PENGARUH KEADILAN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) TERHADAP KINERJA PEGAWAI BADAN PENCARIAN DAN PERTOLONGAN KOTA KENDARI - Novanda, Della Sagita; Nurwati, Nurwati; Mahrani, Sri Wiyati (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims (1) to determine the effect of organizational justice and Organizational Citizenship Behavior (OCB) on employee performance. (2) to determine the effect of organizational justice on employee performance. (3) to determine the effect of Organizational Citizenship Behavior (OCB) on employee performance. The population in this study were 115 employees of the Kendari City Search and Rescue Agency. Because the population is more than 100, the sample size is determined using the Taro Yamane Formula so that a sample of 53 employees is obtained. Data collection methods used in this study were interviews and questionnaires. Furthermore, the data were analyzed using the multiple linear regression analysis method. The results of the analysis show that simultaneously organizational justice and organizational citizenship behavior (OCB) have a positive and significant effect on employee performance. Partially, organizational justice has a positive and significant effect on employee performance. And partially Organizational Citizenship Behavior (OCB has a positive and significant effect on employee performance.